UNIVERSALITAS BAHASA DALAM KONSTELASI PEMBELAJARAN BAHASA ARAB DI INDONESIA - Putra, Wahyu Hanafi (IAIN Batusangkar, Indonesia, 2020)
This study aims to generalize the concept of language universality and its axiology in the context of learning Arabic in Indonesia. The method used in this research was descriptive qualitative. The primary data was the regulation of the Minister of Religion of the Republic of Indonesia No. 2 of 2008 concerning the direction of the Arabic learning curriculum in Indonesia. Secondary data in the form of integrative Arabic learning discourse which helps the validity of primary data. Data were collected through documentation, while data analysis used Miles and Hubermen model, namely data reduction, data presentation, drawing conclusions and verification. A good Arabic learning must have a universality of language value. The universality language is a system of sound symbols that must be complemented by the full and systematic dimensions of language. The principles which have to be followed in the universality of language including phonology, morphology, syntac, and semantic principles. Thus, Arabic language learning constellation in Indonesia using language universality system will be better to improve language dignity.